Evaluation of Clinical and Inflammatory Markers of Nonalcoholic Fatty Liver Disease in Postmenopausal Women with Metabolic Syndrome - Rodrigues, Marcio Hipolito [UNESP]; Bruno, Anderson Souza [UNESP]; Nahas-Neto, Jorge [UNESP]; Sandrim, Valeria C.; Muniz, Ludmila G.; Nahás, Eliana Aguiar Petri [UNESP] (Mary Ann Liebert, Inc, 2014)
Background: The aim of this study was to assess clinical and inflammatory markers in nonalcoholic fatty liver disease (NAFLD) in postmenopausal women with metabolic syndrome.Methods: This cross-sectional study included 180 Brazilian women (age >= 45 years and amenorrhea >= 12 months). Metabolic syndrome was diagnosed by the presence of at least three of the following indicators: Waist circumference (WC) > 88 cm, triglycerides (TGs) >= 150 mg/dL, high-density lipoprotein (HDL) < 50 mg/dL; blood pressure >= 130/85 mmHg; and glucose >= 100 mg/dL. NAFLD was diagnosed by abdominal ultrasound. Participants were divided into three groups: Metabolic syndrome alone (n = 53); metabolic syndrome + NAFLD (n = 67); or absence of metabolic syndrome or NAFLD (control, n = 60). Clinical, anthropometric, and biochemical variables were quantified. The inflammatory profile included adiponectin, interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-alpha). Data were submitted to statistical analysis using a Tukey test, analysis of variance (ANOVA), chi-squared, Pearson correlation, and logistic regression (odds ratio, OR).Results: Women with metabolic syndrome + NAFLD, abdominal obesity, high glucose, and insulin resistance by HOMA-IR were compared to women with metabolic syndrome alone and controls (P < 0.05). High values of IL-6 and TNF-alpha and low values of adiponectin were observed among women with metabolic syndrome alone or metabolic syndrome + NAFLD when compared to controls (P < 0.05). In multivariate analysis, the variables considered as risk of NAFLD development were: High systolic blood pressure (SBP) [(OR 1.02, 95% confidence interval (CI) 1.0-1.04]; large WC (OR 1.07, 95% CI 1.01-1.13); insulin resistance (OR 3.81, 95% CI 2.01-7.13); and metabolic syndrome (OR 8.68, 95% CI 3.3-24.1). Adiponectin levels reduced NAFLD risk (OR 0.88, 95% CI 0.80-0.96).Conclusion: In postmenopausal women, metabolic syndrome, abdominal obesity, and insulin resistance were risk markers for the development of NAFLD, whereas higher adiponectin values indicated a protection marker.